باسم يوسف الخفاجي ملاحظات حول التركيب الكيميائي لاربعة انواع من اسماك هور الحمار\ جنوب العراق - باسم الخفاجي (University of Thi-Qar Journal of Science, 2019)
Protein, Fat and ash content were estimated in the bodies of four species 01 of the Fishes, Barbus luteus, Liza abu , Aspius vorax and Cyprinuscarpio,which were collected from Al-Hammar marsh during Summer July & August/2006 . The results showed that the lower and higher levels of gonado somatic indexand hepato somatic index were 4.2% and 10.37% in L. abu and C. carpio and 0.94% and 1.72% in L. abu and B.luteus respectively .Protein contentwas of the higher ratio 20.5% and 18.5% in the carcass and ovaries of B.luteus, whereas the liver of C.carpio reached higher level 20.3%. Fatcontent recorded higher percentage 6.5% in the carcass of C. carpio , while liver and ovaries in B. luteus recorded higher level 4.9% and 7.4%respectively . It was noted that ash content was of approximated percentage, It was of higher percentage which was1.8% in the carcass of C. Carpio,whereasrecorded higher level 2.3% and 2.5% in the liver and ovaries of B. luteus.  As a conclusion B. luteus and C. carpio have the higher ratio of protein and Lipid in their carcass and ovaries, while they were of the lower levels in thecarcass and ovaries of L.abu and A.vorax. The distribution of the biochemical contents showed a differences in the organs of the same species and among the organs of different species. This is due to many factors among them development of ovaries in all studied species.